Local Epidemics Gone Viral: Evolution and Diffusion of the Italian HIV-1 Recombinant Form CRF60_BC - Lai, Alessia; Simonetti, Francesco Roberto; Brindicci, Gaetano; Bergna, Annalisa; Di Giambenedetto, Simona; Sterrantino, Gaetana; Mussini, Cristina; Menzo, Stefano; Bagnarelli, Patrizia; Zazzi, Maurizio; Angarano, Gioacchino; Galli, Massimo; et al. (Frontiers in Microbiology, 2019)
The molecular epidemiology of HIV-1 in Italy is becoming increasingly complex, mainly due to the spread of non-B subtypes and the emergence of new recombinant forms. We previously characterized the outbreak of the first Italian circulating recombinant form (CRF60_BC), occurring among young MSM living in Apulia between the years 2009-2011. Here we show a five-year follow-up surveillance to trace the evolution of CRF60_BC and to investigate its further spread in Italy. We collected additional sequences and clinical data from patients harboring CRF60_BC, enrolled at the Infectious Diseases Clinic of the University of Bari. Further phylogenetic analyses on more than 10,000 sequences obtained from the national ARCA cohort was performed in parallel. In addition to the 24 previously identified sequences, we retrieved 27 CRF60_BC sequences from patients residing in Apulia, whose epidemiological and clinical features did not differ from those of the initial outbreak, i.e the Italian origin, young age at HIV diagnosis (median 24 years; range 18-37), MSM risk factor (23/25, 92%) and recent infection (from 2008 to 2017). Sequence analysis revealed a growing overall nucleotide diversity, with few nucleotide changes that were fixed over time. Twenty-seven additional sequences were detected across Italy, spanning multiple distant regions. Using a BLAST search, we also identified a CRF60_BC sequence isolated in UK in 2013. Three patients harbored a unique second generation recombinant form in which CRF60_BC was one of the parental strains. Furthermore, this study allowed to identify 13 additional sequences from a clinical center in central Italy (Ancona) that shared a B/C recombination pattern distinct from that detected for CRF60_BC, likely representing a new Italian CRF. Our data show that CRF60_BC gained epidemic importance, spreading among young MSM in multiple Italian regions and increasing its population size in few years, as the number of sequences identified so far has triplicated since our first report. The observed further divergence of CRF60_BC is likely due to evolutionary bottlenecks and host adaptation during transmission chains. Of note, we detected three second-generation recombinants, further supporting a widespread circulation of CRF60_BC and the increasing complexity of the HIV-1 epidemic in Italy.